Application Of Vikor Method To Determine The Location Of Election And Election Care Villages - Winda Amanda (Yayasan Kita Menulis, 2023)
General elections are the core of the democratic process which involves active community participation. In order to realize optimal participation, it is necessary to make efforts to increase public awareness and participation in elections and elections. One effective way is to identify strategic locations to implement the